Peran Pemerintah Dalam Mendukung Industri Kecil Menengah (IKM) di Kabupaten Bojonegoro - Elika Febrianti; Muhammad Bagus Adi Saputra (Journal of Innovative and Creativity, 2025)
This research is motivated by the fact that many industries in Bojonegoro are still not registered for business permits, still rely on simple equipment, their products are not yet optimally marketed digitally, face competition from products outside the region and large industries, and there is minimal involvement of the younger generation in traditional crafts. Therefore, government intervention is needed to assess the effectiveness of government support in increasing the competitiveness of SMEs, identify the policy strategies that have the most impact on local economic growth, and provide recommendations for more targeted government support in digitalization, access to capital, and local product branding. The purpose of this study is to understand the role of the government in supporting small and medium industries (IKM) in Bojonegoro Regency. The approach used is descriptive qualitative, and data was collected through interviews. The respondents in this study consisted of 9 people. The study concluded that the factors affecting industrial businesses in Bojonegoro Regency include licensing, taxation, infrastructure, and labor regulations. These factors are closely related to the government's role in implementing applicable policies.